Menyelidiki Manfaat Ice Breaking Terhadap Fokus Belajar Siswa - Gita Safitriana; Putri Aulia Hakim; Syarifah Syafitri (STAI AL-AMIN, 2025)
Learning in schools often experiences challenges in the form of students' lack of learning focus, especially at the elementary school level. The purpose of applying ice breaking is to help students maintain learning focus during the learning process. This research uses the type of Classroom Action Research (PTK), which is research conducted by teachers in the classroom or in the school where they teach, with an emphasis on perfecting or improving practices and processes in learning. The results show that the use of ice breaking in the learning process plays an important role in creating a meaningful, fun, creative, dynamic and dialogical learning atmosphere. A pleasant learning atmosphere has the potential to encourage students to be more creative and active. The application of ice breaking method in Tahfiz learning in grade 1 elementary school is proven to be effective in supporting students' focus, readiness, and interactivity during the teaching and learning process.